Gender differences in sickness absence and the gender division of family responsibilities - Nikolay Angelov; Per Johansson; Erica Lindahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
This study investigates possible reasons for the gender difference in sickness absence. We estimate both short- and long-term effects of parenthood in a within-couple analysis based on the timing of parenthood. We find that after entering parenthood, women increase their sickness absence by between 0.5 days per month (during the child's third year) and 0.85 days per month (during year 17) more than their spouse. By investigating possible explanations for the observed effect, we conclude that the effect mainly stems from higher home commitment, which reduces women's labour market attachment and, in turn, increases female sickness absence.
Keywords: C23; D13; I19; J22; 330; double burden; health investment; household work; labour market work; moral hazard; parenthood; sickness insurance; work absence; Fehlzeit; Krankheit; Eltern; Weibliche Arbeitskräfte; Arbeitsmarkt; Sozialversicherung; Schweden